Evaluating the Efficacy of the “Support for Life” Program for People with Dementia and Their Families and Carers’ to Enable Them to Live Well: A Protocol for a Cluster Stepped Wedge Randomized Controlled Trial - Goeman, Dianne; Comans, Tracy; Enticott, Joanne C.; Renehan, Emma; Beattie, Elizabeth; Kurrle, Susan; Koch, Susan (Frontiers in Public Health, 2016)
Assistance provided to support people living with dementia and carers is highly valued by them. However current support systems in Australia are disjointed, inaccessible to all, poorly co-ordinated and focus on dysfunction rather than ability. Support workers are in short supply and there is little consistency in their roles. To address this large service gap and unmet need we have developed an evidence-based optimised model of holistic support for people with dementia and their carers and families. This article describes the ‘Support for Life’ model intervention. A stepped wedge cluster randomized controlled trial (SWCRCT) will be conducted over three years across three Australian states. One hundred participants with dementia and/or their carers/family members will be randomly selected from community health centre client lists in each state to receive either the dementia ‘Support for Life’ intervention (Group A) or routine care (Group B). Group A participants will have access to the intervention from year one. Group B participants will continue to receive usual care and will not be denied information on dementia or dementia services in year one. In year two Group B participants will have access to the intervention. A highly trained expert dementia support worker will provide the ‘Support for Life’ intervention, which is a flexible, individually tailored, holistic support that is relationship-centred, focused on enablement as opposed to dysfunction and facilitate participants continued engagement in their community and the workforce. Additionally, dementia education, information resources, advocacy and practical support to navigate and access dementia services and healthcare will be provided. The mode of support will include face to face, telephone and internet, interaction on an ‘as needed basis’ for 12 months. The primary hypothesis is that the intervention will improve the quality of life of people with dementia and the health and wellbeing of carers/family through facilitating the continuation and enhancement of regular daily activities. Secondary hypotheses will examine other health and service usage outcomes. The outputs will also include a health economic analysis to investigate the costs (and savings) of any associated reduction in unnecessary health services use and delay in accessing permanent residential aged care.